2021
DOI: 10.1609/icaps.v31i1.16008
|View full text |Cite
|
Sign up to set email alerts
|

Learning Heuristic Selection with Dynamic Algorithm Configuration

Abstract: A key challenge in satisficing planning is to use multiple heuristics within one heuristic search. An aggregation of multiple heuristic estimates, for example by taking the maximum, has the disadvantage that bad estimates of a single heuristic can negatively affect the whole search. Since the performance of a heuristic varies from instance to instance, approaches such as algorithm selection can be successfully applied. In addition, alternating between multiple heuristics during the search makes it possible to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…These application domains, together with the learning rate control setting from (Daniel et al, 2016), have later been released as part of a benchmark suite, called DACbench (Eimer et al, 2021b), offering a unified interface that facilitates comparisons between different DAC methods across different DAC scenarios. In this article, we extend this initial discussion of Biedenkapp et al (2020) and present a thorough empirical comparison of AC and DAC on these three different realworld DAC applications (Daniel et al, 2016;Shala et al, 2020;Speck et al, 2021) using the unified DACbench interface.…”
Section: Prior Art: Automated Dynamic Algorithm Configurationmentioning
confidence: 67%
See 4 more Smart Citations
“…These application domains, together with the learning rate control setting from (Daniel et al, 2016), have later been released as part of a benchmark suite, called DACbench (Eimer et al, 2021b), offering a unified interface that facilitates comparisons between different DAC methods across different DAC scenarios. In this article, we extend this initial discussion of Biedenkapp et al (2020) and present a thorough empirical comparison of AC and DAC on these three different realworld DAC applications (Daniel et al, 2016;Shala et al, 2020;Speck et al, 2021) using the unified DACbench interface.…”
Section: Prior Art: Automated Dynamic Algorithm Configurationmentioning
confidence: 67%
“…DAC has been an active research area that has produced various highly practical algorithms leveraging dynamic parameter adaptation mechanisms to empirically outperform their static counterparts, e.g., Reactive Tabu Search (Battiti & Tecchiolli, 1994), CMA-ES (Hansen et al, 2003), and Adam (Kingma & Ba, 2015). Beyond these empirical successes and dedicated case studies (e.g., Senior et al, 2013;, the potential of DAC has also been shown theoretically (Moulines & Bach, 2011;Warwicker, 2019;Speck et al, 2021).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations